Teachers' Work Engagement, Burnout, and Interest toward ICT Training: School Level Differences - Stefano Cacciamani; Donatella Cesareni; Caterina Fiorilli; Maria Beatrice Ligorio (MDPI AG, 2022)
Teachers' work engagement is associated with positive outcomes regarding work-related well-being. Conversely, burnout menaces teachers' work and attitudes toward professional development. As indicated in the literature, burnout can influence teachers' work engagement. Considering the impact of ICT on school activities, interest toward ICT training can also affect teachers' work engagement. The present study aims to explore the differences among different school levels concerning work engagement, burnout, and interest toward ICT training. Furthermore, we study the extent to which teachers' burnout and interest toward ICT training predict work engagement, taking into account the school level. The participants were 358 Italian teachers of primary, middle, and high school. We proposed to fill out the Utrecht Work Engagement Scale, the Copenhagen Burnout Inventory, and three ad hoc items assessing interest toward ICT training among 358 Italian teachers. To compare the school levels, an ANOVA and a Multiple regression analysis for each group corresponding to a different school level has been used. Results showed that: (a) primary school teachers have a higher level of work engagement and interest in ICT training compared to their colleagues at high schools; (b) burnout predicts work engagement in all school levels; (c) interest toward ICT training influences work engagement only in primary and high school. Cultural and contextual dimensions are considered when interpreting the results. Implications for teachers' enhancing their commitment at work are discussed, as well as limitations of this study and possible further development.